Biological and analytical investigations of alpha-glucosidase inhibitory and anti-oxidant activities on selected Malaysian medicinal plants - Nooraqilah Che Rozenan,; Nor Hisam Zamakshshari,; Leong, Kok Hoong; Najihah Mohd Hashim,; Khadher Ahmad,; Munirah Abd Razzak,; Zulkifli Mohd Yusof,; Khalijah Awang,; Abd Aziz Ismail,; Rozana Othman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study was performed to establish anti-diabetic and anti-oxidant properties, and to carry out phytochemical analysis of selected local plants which are traditionally used as medicinal plants. Local plants involved in this study were Lawsonia inermis, Punica granatum, Dryobalanops aromatica, Ziziphus mauritiana, and Ocimum basilicum. Solvent extraction was performed using maceration method with solvents of increasing polarity. Alpha-glucosidase inhibition assay was performed on all extracts to ascertain their anti-diabetic potentials. The extracts were screened for antioxidant activity using anti-oxidant assays (FRAP, DPPH, TAOC, ABTS, and BCB) and quantitative phytochemical analyses (TPC and TFC). Chemical profiling using LCMS and GCMS was performed on extracts with high biological activities. Methanol extracts of D. aromatica bark and leaves showed the most potent inhibition of alpha-glucosidase with IC50 values of 0.63 ± 0.03 μg/mL and 0.98 ± 0.02 μg/mL, respectively. Both extracts exhibited similar anti-oxidant activity on all five assays and possessed high phenolic contents with values of 266.79 and 261.69 GAE, respectively. The results obtained suggested that amongst the selected plants studied, D. aromatica showed high anti-oxidant activity and anti-diabetic activity (via inhibition of alpha-glucosidase). This is the first report that highlights the anti-diabetic potential of D. aromatica.